1998
DOI: 10.1046/j.1469-8137.1998.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant defence genes are induced in the pathogenic interaction between bean roots and Fusarium solani, but not in the symbiotic interaction with the arbuscular mycorrhizal fungus Glomus mosseae

Abstract: Plant roots enter symbiotic as well as pathogenic interactions with fungi in the rhizosphere. We studied the response of bean (Phaseolus vulgaris L. cv. Saxa) roots to infection by the arbuscular mycorrhizal fungus Glomus mosseae (Nicol. & Gerd.) Gerdemann & Trappe and the pathogen Fusarium solani (Mart.) Sacc. f. sp. phaseoli (Burkholder) Snyder & Hansen. In a time‐course study of the symbiotic interaction between bean roots and G. mosseae, covering all stages of mycorrhiza development, we detected little cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 51 publications
1
19
0
4
Order By: Relevance
“…Infection of plant tissue by rhizobia and mycorrhiza can induce production of chitinases and defence proteins specific for the interaction (Pozo et al 1999;Salzer et al 2004). PR genes are produced equally, or to a less degree towards rhizobia and mycorrhiza than promoted by a pathogen (Mohr et al 1998). Endophytes typically promote stronger and faster defence responses than pathogens, characterised by production of H 2 O 2 , and elevated activity of the phenylalanine ammonia lyase (PAL) enzyme (Schulz et al 1999;Laukkanen et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Infection of plant tissue by rhizobia and mycorrhiza can induce production of chitinases and defence proteins specific for the interaction (Pozo et al 1999;Salzer et al 2004). PR genes are produced equally, or to a less degree towards rhizobia and mycorrhiza than promoted by a pathogen (Mohr et al 1998). Endophytes typically promote stronger and faster defence responses than pathogens, characterised by production of H 2 O 2 , and elevated activity of the phenylalanine ammonia lyase (PAL) enzyme (Schulz et al 1999;Laukkanen et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…van Dam et al. (2003) point out that there are no known effects of AM fungi on induced defences in plants, as these fungi seem to suppress the defence response of their hosts (Mohr et al. 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, F. solani f. sp. pisi could not induce a defence response in the closely related P. sativum (Mohr et al. , 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments showed that Mt‐chs1 is expressed at a low level also in noninoculated plants. This could have led some authors to conclude that the transcription of CHS, if at all, is only slightly enhanced (Blee & Anderson, 1996; Mohr et al. , 1998).…”
Section: Discussionmentioning
confidence: 99%